ENEM : potencial algébrico na sala de aula - Medeiros, Isabel Cristina (My University, 2026)
This study presents applied research associated with the Professional Master's Program in Science and Mathematics Teaching at the University of Caxias do Sul. The study was conducted with tenth-grade students (first year of High School) at a private school in Rio Grande do Sul. The primary objective was to investigate how to enhance the development of Area 5 Competency from the Enem Reference Matrix through a Didactic Sequence (DS) comprising problem-solving situations. The theoretical framework was based on Ausubel's Meaningful Learning (2003), Zabala and Arnau's competencies (2014), and Clayton Christensen, Michael B. Horn, and Heather Staker's Blended Learning (2013). This descriptive, participant research adopted a qualitative approach and utilized various data collection instruments: diagnostic assessments, forms, questionnaires, and observation logs from both the teacher-researcher and the students. The analysis sought evidence of meaningful learning resulting from the implementation of the planned proposal. Results indicated satisfactory performance, evidenced by the students' interest, engagement, and commitment to the activities and their outcomes. As an educational product, this work resulted in instructional material - developed during the research and refined based on its application - available on the Master's Program website, aimed at supporting teachers in search of innovative approaches for teaching algebra. [resumo fornecido pelo autor]
Este trabalho apresenta uma pesquisa de natureza aplicada, vinculada ao Mestrado Profissional em Ensino de Ciências e Matemática da Universidade de Caxias do Sul, realizada com estudantes da primeira série do Ensino Médio de uma escola privada do Rio Grande do Sul. O objetivo central foi investigar como potencializar o desenvolvimento da competência de área 5 da Matriz de Referência do Enem por meio de uma Sequência Didática (SD) composta por situações-problema. A fundamentação teórica baseou-se na Aprendizagem Significativa de Ausubel (2003), nas competências de Zabala e Arnau (2014) e no Ensino Híbrido Clayton Christensen, Michael B. Horn e Heather Staker (2013). A pesquisa, de caráter descritivo e participante com abordagem qualitativa, utilizou diversos instrumentos para a coleta de dados: avaliação diagnóstica, formulários, questionários e registros de observação, tanto da professora pesquisadora quanto dos estudantes. A análise buscou indícios de aprendizagem significativa a partir da aplicação da proposta planejada. Os resultados apontaram para um desempenho satisfatório, evidenciado pelo interesse, participação e compromisso dos estudantes com as atividades e seus resultados. Como produto educacional, o trabalho resultou em um material didático, proposto na pesquisa e aprimorado a partir da sua aplicação e resultados, que está disponível na página do Mestrado, que visa auxiliar professores em busca de propostas diferenciadas para o ensino da álgebra. [resumo fornecido pelo autor]
Keywords: Aprendizagem significativa; Ensino híbrido; Exame Nacional do Ensino Médio; Álgebra - Estudo e ensino; Meaningful learning; Blended learning; National High School Examination; Algebra - Study and teaching